IN FAMILY RELATIONS ON CHILD EDUCATION - O. Ergasheva; Djamolova Shahnoza (Scholar Express Journal, 2024)
This article discusses the formation of a universal worldview in family relations and the influence of a healthy family environment on child upbringing, psychological features of child upbringing in the family
Keywords: family relations; child upbringing in the family; father